PENGARUH BRAND EXPERIENCE DAN BRAND TRUST TERHADAP BRAND ATTACHMENT SERTA BRAND LOYALTY - Zulfiana Khatimah Ramadhani; Eny Endah Pujiastuti; Hastho Joko Nur Utomo (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2019)
The purpose of this study was to examine the effect of brand experiences on brand attachment, brand trust on brand attachment, brand experiences on brand loyalty, brand trust on brand loyalty, and brand attachment on brand loyalty. The population in this study are customers of Nature Republic skin care products who have made purchases at least 2 times. Population size is infinite. The sample is 118 people aged Nature Republic skin care products, as many as 118 people. Research instrument with a questionnaire. The sampling technique was using systematic random sampling. Data analysis with SEM which is operated with the AMOS application. The results of the study explained that there was a significant influence of brand experiences on brand attachment, brand trust on brand attachment, brand experiences on brand loyalty, brand trust on brand loyalty, and brand attachment on brand loyalty. Keywords: brand experiences, brand attachment, brand trust , brand loyalty,